Sinergi Pendidikan: Mengintegrasikan Bahasa Inggris dan Pembentukan Karakter pada Anak Usia Dini di PAUD Permata Kasih” Pematangsiantar: Pengabdian - Panjaitan, Maru Mary Jones; Purba, Yunis Veronika; Silaban, Cesarina; Manalu, Jespin Saurlina (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This Community Service Program aims to improve English proficiency and character education in early childhood at Permata Kasih Pematangsiantar Early Childhood Education Center. Through seminars involving parents, teachers, and students, we discussed the importance of English education as a tool to improve children's cognitive abilities and character values that support their social and emotional development. Interactive activities, such as fruit and vegetable sticker competitions and fruit satay making, were designed to introduce new vocabulary in English in the context of healthy living. The questionnaire results showed that 100% of respondents agreed that English teaching can improve children's understanding of character and healthy habits. The enthusiasm of the children and parents during the activities showed that learning can be done in a fun way. This program not only succeeded in improving English language skills and character, but also strengthened family relationships. We recommend implementing a sustainable program with more interactive activities and involving more parties in understanding the importance of healthy lifestyles as part of learning..